Association between insurance status and in‐hospital outcomes in patients with out‐of‐hospital ventricular fibrillation arrest. Issue 4 (4th March 2021) - Pancholy, Samir B.; Patel, Gaurav A.; Patel, Dhara D.; Patel, Neil; Pancholy, Shivam A.; Patel, Purveshkumar; Thomas‐Hemak, Linda; Patel, Tejas M.; Callans, David J.
Abstract: Background: Lack of health insurance is associated with adverse clinical outcomes; however, the association between health insurance status and in‐hospital outcomes after out‐of‐hospital ventricular fibrillation (OHVFA) arrest is unclear. Hypothesis: Lack of health insurance is associated with worse in‐hospital outcomes after out‐of‐hospital ventricular fibrillation arrest. Methods: From January 2003 to December 2014, hospitalizations with a primary diagnosis of OHVFA in patients ≥18 years of age were extracted from the Nationwide Inpatient Sample. Patients were categorized into insured and uninsured groups based on their documented health insurance status. Study outcome measures were in‐hospital mortality, utilization of implantable cardioverter defibrillator (ICD), and cost of hospitalization. Inverse probability weighting adjusted binary logistic regression was performed to identify independent predictors of in‐hospital mortality and ICD utilization and linear regression was performed to identify independent predictors of cost of hospitalization. Results: Of 188 946 patients included in the final analyses, 178 005 (94.2%) patients were insured and 10 941 (5.8%) patients were uninsured. Unadjusted in‐hospital mortality was higher (61.7% vs. 54.7%, p  < .001) and ICD utilization was lower (15.3% vs. 18.3%, p  < .001) in the uninsured patients. Lack of health insurance was independently associated with higher in‐hospital mortality (O.R = 1.53, 95% C.I. [1.46–1.61]; p  < .001) and lower utilization of ICD (O.R = 0.84, 95% C.I [0.79–0.90], p  < .001). Cost of hospitalization was significantly higher in uninsured patients (median [interquartile range], p ‐value) ($) (39 650 [18 034‐93 399] vs. 35 965 [14 568.50‐96 163], p  < .001). Conclusion: Lack of health insurance is associated with higher in‐hospital mortality, lower utilization of ICD and higher cost of hospitalization after OHVFA.